1988
DOI: 10.1007/bf00330617
|View full text |Cite
|
Sign up to set email alerts
|

An RFLP adjacent to the maize waxy gene has the structure of a transposable element

Abstract: Two maize inbred lines harbor non-mutant waxy (Wx) genes that display restriction fragment length polymorphism (RFLP) upstream from the start of Wx transcription. Sequencing of this region in the two strains revealed a DNA insertion with the structural features of a transposable element. The insertion is 316 bp in length, has 15 bp imperfect inverted repeats and is flanked by a 5 bp direct repeat generated upon insertion. Sequences homologous to this insertion are present in multiple copies in maize and its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Furthermore, preliminary studies have identified three additional MITE families with 5,000-12,000 copies per haploid genome [B2 (5), mPIF (Q.Z. and S.R.W., unpublished data) and Hb2 (37)], that, like Hbr, have polymorphic insertion sites in genic regions of maize (Q.Z., N. Jiang, and S.R.W., unpublished data). Given the high copy numbers of the four families, these data indicate that the presence or absence of MITEs is a significant contributory factor to the high level of polymorphism shown previously to be characteristic of maize genes (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preliminary studies have identified three additional MITE families with 5,000-12,000 copies per haploid genome [B2 (5), mPIF (Q.Z. and S.R.W., unpublished data) and Hb2 (37)], that, like Hbr, have polymorphic insertion sites in genic regions of maize (Q.Z., N. Jiang, and S.R.W., unpublished data). Given the high copy numbers of the four families, these data indicate that the presence or absence of MITEs is a significant contributory factor to the high level of polymorphism shown previously to be characteristic of maize genes (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…At the 3′ end, the glu1 and mu3.7 mzsTn-1 repeat units differ by two nucleotides, but again they each differ from the wx and B-I mzsTn-1s by up to 9 nucleotides, indicating much higher divergence at the 3′ ends of these homologous elements. It is conceivable that the 25 bp long terminal inverted repeat we postulate is actually 15 bp, as proposed by Spell et al(1988), and that the remaining 10-bp segment is involved in the formation of intra-strand DNA secondary structures (e.g., hairpin and stem-loop), as suggested by Bureau and Wessler (1992) for members of the Tourist family of small transposons.…”
Section: Intron 4 Insertion and Its Relation To Other Small Transposonsmentioning
confidence: 92%
“…It is apparent that mzsTn-2 is a member of the Stowaway family of inverted repeat elements that has recently been catalogued and described (Bureau and Wessler 1994b). The Stowaway family elements occur widely in both monocots and dicots and vary (Spell et al 1988) and in the glu1 (this study), mu3.7 (Leader et al 1994), and B-I (Radicella et al 1992) genes, all of maize. The white letters with black background in the alignment show identities among the sequences of the four different elements, while the black letters with white background show the differences.…”
Section: Intron 10 Insertion and Its Relation To Other Small Transposonsmentioning
confidence: 94%
See 1 more Smart Citation
“…It has also become evident that non-long terminal repeat (LTR) retrotransposons are abundant in maize, as well as other plant genomes (33,34). Many additional maize transposon families have been identified through their sequence organization and their presence in or near genes (35)(36)(37)(38)(39)(40). We now know that transposons and retrotransposons comprise half or more of the maize genome (41).…”
Section: Plant Transposons In the Age Of Genomicsmentioning
confidence: 99%